Association between Nonalcoholic Fatty Liver Disease and Colon Polyps: A Case-Control Study in Taiwan - Kuan-Fu Liao; Pei-Ying Chung; Yu-Hung Kuo; Shih-Wei Lai (International Journal of Clinical Practice)
Objective. To investigate the potential association between nonalcoholic fatty liver disease (NAFLD) and colon polyps in Taiwan. Methods. We utilized 2006–2015 claims data of the Taiwan National Health Insurance Program as a data source. A case-control study was conducted, involving individuals 20 years or older with and without colon polyps. Cases comprised individuals diagnosed with colon polyps, identified through diagnosis codes. Controls were selected from individuals without colon polyps, matched to cases based on sex, age, and comorbidities. NAFLD was identified based on diagnosis codes. The logistic regression model with odds ratio (OR) and 95% confidence interval (CI) was employed to assess the association between NAFLD and colon polyps. Results. The study included 16,890 cases with colon polyps and 67,560 matched controls without colon polyps. The mean age was 57 years old and about 61% of study subjects were males. Among cases with colon polyps, 1.0% had a diagnosis of NAFLD, whereas only 0.4% exhibited NAFLD in the control group. After adjustment for confounding variables, a multivariable logistic regression model revealed a statistically significant association between NAFLD and colon polyps, with an odds ratio of 2.32 (95% CI = 1.91–2.82). Conclusion. This case-control study suggests a positive association between NAFLD and colon polyps. These results contribute to our understanding of the potential links between NAFLD and gastrointestinal health.